2023
DOI: 10.3390/cancers15133373
|View full text |Cite
|
Sign up to set email alerts
|

Acinic Cell Carcinoma in the 21st Century: A Population-Based Study from the SEER Database and Review of Recent Molecular Genetic Advances

Abstract: Background: Acinic cell carcinoma (AciCC) comprises 6–7% of all salivary gland neoplasms and is the second most common salivary gland malignancy in children. Like many salivary gland carcinomas, it is considered low grade but occasionally it behaves aggressively. Understanding the risk factors associated with recurrence, metastasis, and death is important to determine the counseling and management of individual patients. Older population-based studies are presumed to have been confounded by the misclassificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Few articles have reported curative radiotherapy for primary AcCC, and the treatment’s efficacy remains controversial. 2 , 3 , 12 For the treatment of skull base AcCC, two studies reported that conformal radiation therapy and intensity-modulated radiation therapy were applied for local tumor control and led to survival for several years; these cases may indicate that some AcCCs exhibit radiosensitivity. 1 , 13 Nevertheless, given the tenacious tendency to recur, repeat extensive radiotherapy to the skull base might jeopardize adjacent cranial nerves and brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Few articles have reported curative radiotherapy for primary AcCC, and the treatment’s efficacy remains controversial. 2 , 3 , 12 For the treatment of skull base AcCC, two studies reported that conformal radiation therapy and intensity-modulated radiation therapy were applied for local tumor control and led to survival for several years; these cases may indicate that some AcCCs exhibit radiosensitivity. 1 , 13 Nevertheless, given the tenacious tendency to recur, repeat extensive radiotherapy to the skull base might jeopardize adjacent cranial nerves and brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Male gender, tumor grade, distant metastasis, age more than 50 years, and size more than 4 cm are associated with a bad prognosis in ACC. [9] The classical type of acinic cell carcinoma is the least aggressive with low malignant potential. Still, the papillary cystic variant or carcinomas with undifferentiated cells in the medullary pattern are more aggressive fatal tumors.…”
Section: Discussionmentioning
confidence: 99%